Body of Knowledge of Islamic Education Teachers: Critical Review of the Curriculum Master Program of Islamic Education Ahmad Dahlan University Yogyakarta - Hanafi, Muhammad Hafizh; Suyadi, Suyadi (ISLAMIKA, 2024)
Focus this study will review the islamic education teacher body of knowledge critically with regard to three main issues regarding the problematic development of the curriculum in tertiary institutions including namely; agreement between cpl (graduate learning outcomes), relevance, andconstructive alignment, with the context of the body of knowledge of islamic education teacher . the purpose of this study is to analyze and critically review the body of knowledge, islamic education teacher curriculum at the ahmad dahlan university islamic education teacher masters program. methods the method applied in this study is a qualitative method with a type of field study orfield study. the setting in this research is the islamic education teacher study program at ahmad dahlan university, yogyakarta. the results of the research in this study are that it has implemented the body of knowledge of islamic education teacher with appropriate courses includingal-quran education, hadith education, belief education, moral education, date education, arabic language education.and is an embryo of a derivative of contemporary courses. this is proven by the output of each course in the form of publication of national or international indexed journal articles and intellectual property rights as well as a simple patent.